Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.athoracsur.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pulmonary Hypertension on Patients With Idiopathic Pulmonary Fibrosis Awaiting Lung Transplantation

Abstract: The manifestation of PH, even with mild severity, is associated with significantly increased risk for death among patients with idiopathic pulmonary fibrosis awaiting lung transplantation, so referral should be considered early in the disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 38 publications
3
42
1
2
Order By: Relevance
“…PH is a common comorbid condition in patients with many forms of chronic lung disease (CLD) [43]. CLD-associated pulmonary hypertension (CLD-PH) has been shown to be associated with reduced functional status and worse outcomes [44,45]. The most well characterized CLD-PH entities are chronic obstructive pulmonary disease (COPD), the idiopathic interstitial pneumonias (IIP) including idiopathic pulmonary fibrosis (IPF), and sarcoidosis.…”
Section: Update On Group 3 Phmentioning
confidence: 99%
“…PH is a common comorbid condition in patients with many forms of chronic lung disease (CLD) [43]. CLD-associated pulmonary hypertension (CLD-PH) has been shown to be associated with reduced functional status and worse outcomes [44,45]. The most well characterized CLD-PH entities are chronic obstructive pulmonary disease (COPD), the idiopathic interstitial pneumonias (IIP) including idiopathic pulmonary fibrosis (IPF), and sarcoidosis.…”
Section: Update On Group 3 Phmentioning
confidence: 99%
“…Following diagnosis, the median survival time is approximately 2-3 years and treatment options are limited [1]. Pulmonary hypertension (PH), defined as an elevation of resting mean pulmonary arterial pressure (MPAP) to ⩾25 mmHg, is a well-recognised complication in advanced IPF which is associated with higher mortality rates [2][3][4][5]. While the upper level of normal for MPAP is 20 mmHg, the significance of MPAP levels between 21 and 24 mmHg remains unclear in terms of their prognostic and therapeutic implications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence that pulmonary hypertension (PH) associated with lung disease is a predictor of disease severity and mortality in patients awaiting LTX (5)(6)(7). Patients with PH suffer hypoxia, hypercapnia and respiratory acidosis, as a result of increased peripheral vascular resistance and right heart failure (8,9); these conditions can eventually lead to death.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PH suffer hypoxia, hypercapnia and respiratory acidosis, as a result of increased peripheral vascular resistance and right heart failure (8,9); these conditions can eventually lead to death. Previous studies have reported that PH, when confirmed by cardiac catheterization, is an independent predictive factor for survival after LTX (7,(10)(11)(12)(13). In addition, several studies have also analyzed post-LTX prognosis via echocardiography (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%